Hujjiyah Nazariyah Saddiaz-Żarāiʻfī al-Fiqh al- Islāmywatatbīquhāfī Qadāyāal-Maʹkȗlātwa al- Mashrȗbātwa al-Malbȗsāt - Imam Sujoko (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
This study entitled:HujjiyahNazariyahSaddiaz-Żarāiʻfī al-Fiqh al-IslāmywatatbīquhāfīQadāyāal- Maʹkȗlātwa al-Mashrȗbātwa al-Malbȗsāt, deal with the theory ofSaddiaz-Żarāi. The study tries to explore its meaning, concept, and its legality in Islamic jurisprudence, and how it could be implemented in the cases of food, drink and clothing. Food, drink and clothing are the primary need of human, but there are some cases faced by Muslim related to the food, drink and clothing. For example a Muslim will consume a product of food or drink or clothingthat produced from the non Muslim country which they do not mind about the material; halal or haram. Should Muslim stops from using those product, based on the theory of Saddiaz-Żarāiʻ?. The study found that the theory of Saddiaz-Żarāiʻ,is a one of the Islamic resources regarding to the majority of Muslim scholar, event there are some differences among them related to its implementation. And some Muslim scholar does not recognize Saddiaz-Żarāiʻ as Islamic resources. But for those who agree with the theory ofSaddiaz-Żarāiʻ,they should understand the regulation of Saddiaz-Żarāiʻ. The methodology of study is library study which is referring to the Islamic references such as texts of Qur’an and hadis and its exegesis, Islamic jurisprudence books both classic and modern book, and fatwa of modern Muslim scholarsDOI: 10.15408/insaniyat.v2i1.6591